School meets street: Exploring the links between low achievement, school exclusion and youth crime among African-Caribbean boys in London - Liz Spencer; James Scott (University of Essex, Institute for Social and Economic Research (ISER), 2013)
This paper explores the process that links low achievement, school exclusion and involvement in crime among African-Caribbean boys and young men. Based on qualitative interviews with pupils and teachers at a pioneering secondary school in London and also with African-Caribbean young men who had dropped out of or been excluded from other schools in the area, we identify key aspects of 'trouble at school' and ways in which this can lead to 'trouble on the street'. When students experience academic or behavioural problems they may drop out of or be formally excluded from school. Although schools are responsible for arranging alternative provision, in practice, once out of mainstream education, students are unlikely to gain academic qualifications and the problem of low achievement is exacerbated. They are then at a disadvantage in the job market, and their perceived lack of legitimate opportunities for making money may lead them to engage in crime. A complex interplay of factors appears to influence this low achievement - school exclusion - crime sequence, including the young person's family background, their neighbourhood, and the culture in which they are embedded. According to the students who took part in school interventions the main benefits of participation were seen as: being part of a community of support; improved motivation; higher academic achievement; the ability to express emotions constructively; and a greater sense of responsibility and self- worth. Our research suggests that by adopting an inclusive rather than exclusive policy, schools can buy time, retaining vulnerable young men within the educational system, keeping their options open until they have a chance to mature, rather than leaving them to the uncertainty of 'the street'.
Keywords: 330; low achievement; school exclusion; youth crime; gangs; school interventions